Epidemiological pattern of severe malocclusions in Brazilian adolescents - Peres, Karen Glazer; Frazao, Paulo; Roncalli, Angelo Giuseppe (Revista de Saúde Pública, 2013)
OBJECTIVE: To describe the distribution of malocclusion and its associated factors in Brazilian adolescents. METHODS: Data from 7,328 subjects aged 12 years and 5,445 adolescents aged 15-19 years were analyzed. The adolescents took part in the Brazilian Oral Health Survey (SBBrasil 2010). The outcome was severe malocclusion according to the dental aesthetic index. The independent variables were sex, skin color, monthly household income, possessions, number of individuals in the household, untreated dental caries, missing teeth and dental appointments or lack thereof, frequency, and reason. Logistical regression analysis was carried out, considering the complex sampling cluster design, based on a hierarchical model. RESULTS: The prevalence of severe malocclusion was 6.5% and 9.1% in the 12-year-olds and the 15-19-year-olds, respectively. After adjustment, those with lighter- skinned black or black skin were 1.59 (95%CI 1.08;2.34) times more likely to present the outcome compared with those with white skin. The loss of one or more first molars increased 2.66 (95%CI 1.26;5.63) the chance to present severe malocclusion by the age of 12. Adolescents aged 15-19 whose household income was below R$ 1,500.00 (OR 2.69 [95%CI 1.62; 4.47]) and those who had seen a dentist for treatment (OR 2.59 [95%CI 2.55;4.34]) had the greatest chance of having severe malocclusion compared with those with higher incomes and those who visited the dentist for prevention.